Study of Aesthetic Forms and Symbolic Meaning of Gayor Gong Senen Relief Carving at Rumah Kartini, Jepara - Farokhi, Sakhron; Haryanto, Eko; Yusof, Nurhikma Bt Mat (Universitas Negeri Semarang, 2025)
In 2014, Rumah Kartini created a replica of a historical heritage artwork from Jepara's carving culture and pioneered the reproduction of the Gayor Gong Senen relief. The research location was at Rumah Kartini, Pengkol, Jepara Regency. Data collection techniques included observation, interviews, and document review. The data were then analyzed through data reduction, data presentation, and verification or conclusion. This research employed a qualitative descriptive method. The study aimed to understand the creation process, aesthetic forms, and symbolic meaning of the Gayor Gong Senen carved relief. The results showed that the creation process consisted of five stages: research, motif sketching, construction, carving, and finishing. The aesthetic form of the Gayor Gong Senen relief lies in the organization of elements such as lines, space, planes, color, texture, and light-dark contrasts, creating an engaging composition. Balance and proportion in the carving, as well as rhythm and dominance in the motif patterns, serve as the main attractions, forming a cohesive artistic piece. The symbolic meaning conveyed through the Gayor Gong Senen relief includes religious values and philosophical messages about human life within society, particularly in Javanese culture.